1997
DOI: 10.1177/146900479700100203
|View full text |Cite
|
Sign up to set email alerts
|

A review of the reported attitudes of health and social care professionals towards people with learning disabilities: implications for education and further research

Abstract: The investigation of attitudes towards people with disabilities has been a consistent research focus for the past 20 years. It appears that during the past decade, in particular, a considerable amount of attention has been invested in investigating the attitudes of a range of health and social care professionals towards people with learning disabilities. Indeed this has been the specific focus of several recent studies. This paper reviews recent research findings concerning the attitudes of health and social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…Factor 3 reflects that when professionals do not receive training on LDs, they have reduced confidence and ability in working effectively with such clients. In contrast with conclusions by Fitzsimmons and Barr () that no relationship between attitudes and education is established, Factor 3 demonstrates a strong association between the two. Furthermore, lack of knowledge on LDs resulted in discrepancies within therapists’ responses.…”
Section: Discussioncontrasting
confidence: 98%
“…Factor 3 reflects that when professionals do not receive training on LDs, they have reduced confidence and ability in working effectively with such clients. In contrast with conclusions by Fitzsimmons and Barr () that no relationship between attitudes and education is established, Factor 3 demonstrates a strong association between the two. Furthermore, lack of knowledge on LDs resulted in discrepancies within therapists’ responses.…”
Section: Discussioncontrasting
confidence: 98%
“…It is anticipated that the provision of opportunities for police officers to meet people with ID in facilitated settings, where they can demonstrate their abilities and also discuss their needs, will further increase the positive attitudes of police officers by directly challenging stereotypes about people with ID. Such an approach is supported by the growing evidence that direct contact with people with ID in settings where they can demonstrate their skills facilitates a positive change of attitude towards people with ID (Fitzsimons & Barr 1997).…”
Section: Discussionmentioning
confidence: 99%
“…2004). Unfavourable attitudes towards people with intellectual disabilities have been found to exist amongst a range of health and social care professionals (Bickley 1990; Fitzsimons & Barr 1997; Nursey et al. 1990) and researchers have suggested that this may partly explain inequalities in health care for this population (Howells 1986; Scott & Routledge 1997).…”
Section: Introductionmentioning
confidence: 99%